2016
DOI: 10.5114/pjp.2016.63774
|View full text |Cite
|
Sign up to set email alerts
|

Keratin 7 expression in lymph node metastases but not in the primary tumour correlates with distant metastases and poor prognosis in colon carcinoma

Abstract: Colorectal carcinoma (CRC) is one of the leading causes of cancer-related deaths worldwide. Alterations in keratin expression, including keratin 7 (K7), are frequent findings in multiple cancers, and they constitute a prognostic factor. The aim of our study was to evaluate the prognostic significance of K7 in the primary tumour and lymph node metastases in two separate cohorts of patients: the first one with lymph node involvement (LN+, 129 cases) and the second one free of LN metastases (LN-, 85 cases). Kerat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 24 publications
0
20
0
Order By: Relevance
“…Studies have demonstrated that keratins play a vital role in maintaining the mechanical stability and integrity of epithelial cells, and participate in several intracellular signaling pathways involved in cell stress, proliferation, and metastasis 27 , 28 . Numerous studies have found several genes that were specifically upregulated or downregulated in CRC tissues and could be used as biomarkers for diagnosis or prognosis 25 , 29 . KRT80 has been rarely reported to be associated with any disease, including cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have demonstrated that keratins play a vital role in maintaining the mechanical stability and integrity of epithelial cells, and participate in several intracellular signaling pathways involved in cell stress, proliferation, and metastasis 27 , 28 . Numerous studies have found several genes that were specifically upregulated or downregulated in CRC tissues and could be used as biomarkers for diagnosis or prognosis 25 , 29 . KRT80 has been rarely reported to be associated with any disease, including cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, we detected an upregulation of several keratins and keratin associated proteins ( Table 1 ), whose function for tumorigenesis and progression is still not fully understood yet. Keratin 7 seems to be involved in metastasis in colon carcinoma [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Every type of epithelial cell often possesses a specific cytokeratin expression profile that distinguish from others. In malignant transformation and progression, although tumors largely keep the cytokeratin profiles, the expression levels of cytokeratins are diverse . Aberrant expression of cytokeratins in tumor cells usually predicts a poor clinical outcome.…”
Section: Discussionmentioning
confidence: 99%